2003
DOI: 10.1001/archinte.163.11.1285
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Recurrent Venous Thromboembolism After Treatment With Vitamin K Antagonists in Relation to Time Since First Event

Abstract: There is a diminishing risk of recurrent venous thromboembolism over time and a stabilization after 9 months independent of the duration of the initial treatment with vitamin K antagonists. These findings have important implications for decision making about the optimal duration of treatment with vitamin K antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 121 publications
1
39
0
4
Order By: Relevance
“…Although anticoagulation is effective in preventing recurrence, the duration of anticoagulation does not affect the risk of recurrence once primary therapy for the incident event is stopped. 10,11 Independent predictors of recurrence include male gender, 12 increasing patient age and body mass index, neurological disease with leg paresis, and active cancer. 6,9,10,13 Additional predictors include "idiopathic" venous thromboembolism, 13 a lupus anticoagulant or antiphospholipid antibody, 14,15 antithrombin, protein C or protein S deficiency, 16 and possibly persistently increased plasma fibrin D-dimer 17 and residual venous thrombosis.…”
Section: Venous Thromboembolism Recurrencementioning
confidence: 99%
“…Although anticoagulation is effective in preventing recurrence, the duration of anticoagulation does not affect the risk of recurrence once primary therapy for the incident event is stopped. 10,11 Independent predictors of recurrence include male gender, 12 increasing patient age and body mass index, neurological disease with leg paresis, and active cancer. 6,9,10,13 Additional predictors include "idiopathic" venous thromboembolism, 13 a lupus anticoagulant or antiphospholipid antibody, 14,15 antithrombin, protein C or protein S deficiency, 16 and possibly persistently increased plasma fibrin D-dimer 17 and residual venous thrombosis.…”
Section: Venous Thromboembolism Recurrencementioning
confidence: 99%
“…[5][6][7] Since the risk of vitamin K antagonist-related bleeding does not decrease with time 3 months after the start of therapy 8 (but indeed increases with age), the benefit of prolonged vitamin K antagonism diminishes over time. Indefinite secondary prophylaxis with vitamin K antagonists in all patients with previous unprovoked VTE should, therefore, be carefully assessed and should be limited to those patients with the highest risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in a meta-analysis by Van Dongen and colleagues it was demonstrated that the recurrence risk after VTE did not depend on the duration of treatment, although this concerned a study of patients with a first VTE. 4 The lack of long-term follow-up data of the larger population from which our study subjects were derived, i.e. all patients with a diagnosis of first or recurrent VTE, did not allow us to compare the recurrence rate after a second VTE to that after a first VTE.…”
Section: -13mentioning
confidence: 99%
“…The rationale for the latter recommendation is that patients with a late second VTE have a relatively limited risk of recurrent VTE, which is supported by indirect evidence that the risk of VTE recurrence is highest shortly after cessation of anticoagulant treatment for a first VTE and then rapidly decreases. 4,5 Taking into account that the anticoagulant-associated risk of hemorrhage persists while anticoagulant treatment is continued and considerably increases with age, it is argued that the risk of hemorrhage associated with long-term anticoagulant treatment may outweigh the reduction of risk of recurrent VTE associated with continued anticoagulant treatment in such circumstances. 6 In accordance with the Dutch multidisciplinary guidelines, a limited duration of treatment of 12 months has been systematically considered in all patients diagnosed with a late second VTE since 2003 in the Department of Thrombosis and Hemostasis of our hospital.…”
Section: Introductionmentioning
confidence: 99%